Entrepreneurship in the age of empire : colonialism, collaboration and exploitation - Dietz, Sarah, 1965- (New York, NY : Routledge, 2021)
"This book illustrates how entrepreneurial styles formed and evolved in the post-family capitalist era, how ambitious businessmen navigated socio-commercial networks, or the group system, to gain access to a highly-integrated system of capital cooperation, to disguised monopolies and interests interlinked"--
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship; Imperialism; Capitalism; BUSINESS & ECONOMICS / Corporate & Business History; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / International / General